2019
DOI: 10.1007/s12298-019-00644-w
|View full text |Cite
|
Sign up to set email alerts
|

Bletilla striata: a review of seedling propagation and cultivation modes

Abstract: In recent years, the domestic and international market demand for Bletilla striata has increased rapidly because of its wide use in medical, pharmaceutical, chemical, health, cosmetology, and other fields. The increased demand and a shortage of wild herbal resources have led to the development of large-scale introduction and cultivation programs. Using our research results and the relevant literature, this paper characterizes the original B. striata plant, as well as seedling propagation techniques and its mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…It is a common experimental method to optimize the culture medium using the orthogonal test method. Zhang selected 1/2 MS medium as the basic medium, with 1% NaClO, 2% sucrose, and 0.1% activated carbon, with which the seed germination rate of B. striata attained 80% (Zhang et al 2019). In our experiment, we found that the optimal media ratio for seed germination was MS + 6-BA (2.0 mg/L) + NAA (1.0mg/L), under which the germination rate was effectively improved up to 91.8%.…”
Section: Discussionmentioning
confidence: 99%
“…It is a common experimental method to optimize the culture medium using the orthogonal test method. Zhang selected 1/2 MS medium as the basic medium, with 1% NaClO, 2% sucrose, and 0.1% activated carbon, with which the seed germination rate of B. striata attained 80% (Zhang et al 2019). In our experiment, we found that the optimal media ratio for seed germination was MS + 6-BA (2.0 mg/L) + NAA (1.0mg/L), under which the germination rate was effectively improved up to 91.8%.…”
Section: Discussionmentioning
confidence: 99%
“…After tubers are collected from the plant, they are peeled and dried. People use that plant for bleeding, muscular damage, burns, skin wounds, ulcers and, liver tumours (Xiang et al, 2013;Wang et al, 2013;Peng et al, 2014;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…f. (Orchidaceae), named "Bai Ji" in Chinese, belongs to the orchidaceous family and is distributed widely in eastern Asian countries, including China, North Korea, Japan, and Burma [1,2]. B. striata has been widely used in traditional Chinese herbal medicine (TCM) for thousands of years and is one of the "seven white" in ancient China, mainly distributed in the Qinling Mountains and Yangtze River region [3,4]. TCM holds that B. striata is bitter, astringent, neutral, and warm and has bioactivities in alimentary canal mucosal damage, ulcers, bleeding, bruises, and burns [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…B. striata has been widely used in traditional Chinese herbal medicine (TCM) for thousands of years and is one of the "seven white" in ancient China, mainly distributed in the Qinling Mountains and Yangtze River region [3,4]. TCM holds that B. striata is bitter, astringent, neutral, and warm and has bioactivities in alimentary canal mucosal damage, ulcers, bleeding, bruises, and burns [4,5]. Also, the functions of hemostasis, detumescence, and improving one's health of B. striata were recorded by Chinese pharmacopeia (2010) [2,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation